Development of SNP for Sebastes Species Identification With Special Focus on the Cryptic Species Complex of Sebastes norvegicus - Torild Johansen; Tanja Hanebrekke; Francois Besnier; Jon Ivar Westgaard; Ingrid Marie Bruvold; Geir Dahle; Laila Unneland; Helle Torp Christensen; Atal Saha (Ecology and Evolution)
ABSTRACT The genus Sebastes in the North Atlantic comprises of long lived deep‐waters species that have been extensively fished upon, and many stocks are severely depleted across the Atlantic. This is particularly evident for the species Sebastes norvegicus. In recent papers, cryptic species have been indicated within this genus and molecular markers are therefore needed to provide identification for the Sebastes species, including the cryptic species as a basis for advice regarding management and rebuilding of the stocks. A suite of 2800 Single Nucleotide Polymorphism (SNP) markers were identified from ddRAD sequencing data, of which 56 SNPs were organized in two multiplex reactions and tested on 191 Sebastes spp. from different sampling locations from Norway and Greenland. Good‐quality amplification products were successfully obtained from 49 SNP markers for Sebastes species ID, and 3 TaqMan probes were designed to successfully assign S. mentella, S. viviparus, and the two cryptic species S. norvegicus types A and B. A total 47 SNPs were biallelic, with averaged HE per locus ranging between 0.053 and 0.50. This SNP‐based method establishes a foundation for genetically identifying the Northeast Atlantic Sebastes species. The findings presented should be followed by an effort to look for morphological characters to recognize the S. norvegicus cryptic species on site. In general, the SNP markers are a proper tool for monitoring the distribution of the species from a management perspective.